ANALYSIS OF THE EFFECT OF FIXED ASSETS ON THE STOCK PRICE OF THE COMPANY INDEXED LQ45 ON THE INDONESIA STOCK EXCHANGE - Dwi Urip Wardoyo; Liana Suci Karnila Manurung; Novia Egita Br. Tarigan (GoAcademica Research dan Publishing, 2021)
The purpose of this research is to examine the effect of fixed assets and the impact of these variables on stock prices. The population used are companies that are included in the LQ45 index contained in the IDX with a period of 3 years (2018-2020). The number of samples used were 15 companies and used a purposive sampling method using the SSPS (Statistical Package for Social Science) program testing program. The results of this study are fixed assets in the company have a positive effect on shares.